A revised catalogue of earthquaqes in the broader area of Greece for the period 1950-2000 - PAPANASTASSIOU, D.; LATOUSSAKIS, J.; STAVRAKAKIS, G. (Bulletin of the Geological Society of Greece, 2001)
An earthquake catalogue for Greece and the surrounding areas for the time period 1950 - 2000, is presented. This catalogue contains more than 59,000 earthquakes recorded and located by the seismological network of the Institute of Geodynamics, National Observatory of Athens. The accuracy of the determinations of the source parameters as well as the completeness of the catalogue have been improved significantly, but they vary according to the period of observation as both depend on the number and quality of the seismological stations consisting the network. This revised catalogue is listed on the Worldwide Web Page http//www.gein.noa.gr, of the Institute of Geodynamics